2008
DOI: 10.1007/s11458-008-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl chloride) composite emulsion resins modified by polyurethane

Abstract: An ionomer-type of polyurethane (PU) emulsion was prepared from toluene diisocyanate (TDI), polypropylene glycol (PPG) and dimethylol propionic acid (DMPA) following a self-emulsification process. The modified poly(vinyl chloride) (PVC) emulsion resin was obtained by in situ emulsion copolymerization using the PU as seeds in an autoclave. The effects of PU molecular weight on the mechanical properties and thermal stability of the PU/PVC materials were investigated. The composite latex particles and composite m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Barring this, the residual four sample color change magnitudes are smaller than the blank, with only slight alteration following 9-h irradiation. Liu et al [39] conducted research on the impact of ultraviolet absorbers on the UV resistance of PUR. The study revealed that the system with added ultraviolet absorbers was more stable compared to the system without such additives, as evidenced by the increased retention of tensile strength and elongation at break.…”
Section: Chromatic Aberrationmentioning
confidence: 99%
“…Barring this, the residual four sample color change magnitudes are smaller than the blank, with only slight alteration following 9-h irradiation. Liu et al [39] conducted research on the impact of ultraviolet absorbers on the UV resistance of PUR. The study revealed that the system with added ultraviolet absorbers was more stable compared to the system without such additives, as evidenced by the increased retention of tensile strength and elongation at break.…”
Section: Chromatic Aberrationmentioning
confidence: 99%